Validity of point-of-care device for diagnosing anemia in workers exposed to lead - Viramgami, Ankit; Soundarajan, Soundarya; Sheth, Ankit; Upadhyay, Kuldip (Indian Journal of Community Health, 2022)
Detecting anemia in occupational health settings is critical in a high-risk population for anemia like the lead-exposed. Whether the point-of-care devices are sensitive to detect anemia in individuals with high levels of lead exposure is unknown. We compared hemoglobin (Hb) levels from HemoCue® Hb 301 System and standard analyzer, Mindrey-BC 5300, in individuals (n=58) exposed to lead (mean levels = 44.9 ?g/dL) for a chronic period (mean duration of exposure = 105 months). We observed high sensitivity (0.95), specificity(0.95) in detecting anemia by hemocue, and high agreement between the methods. The significant difference in Hb values between the methods (0.171g/dL, p=0.018) was clinically minimal. We conclude that hemocue is a good method for rapidly detecting anemia and estimating Hb levels among the lead-exposed in resource-limited settings.